Potential Tools to Support Learning: OpenAI and Elevenlabs Integration - Roro Ayu Fasha Dewatri; Achmad Zahin Al Aqthar; Handi Pradana; Betuah Anugerah; Wakhid Herri Nurcahyo (SEAMEO SEAMOLEC, 2023)
The development of technology in education has grown significantly, where technology is now a principal aspect in the communication, storage and transfer of information, as well as the production of audio-visual media. This article discusses the design and implementation of combining two innovative technologies, OpenAI and Elevenlabs, to create potential learning aids. OpenAI, using generative language models such as GPT-3, provides an opportunity to develop virtual assistants with realistic communication capabilities in a learning context. In contrast, Elevenlabs offers voice artificial intelligence technology that enables the creation of highly realistic human voices in multiple languages. The utilisation of Raspberry Pi as hardware provides flexibility in controlling the interaction between AI and physical devices. Third-party platforms from OpenAI and ElevenLabs enable realistic and effective voice interaction in educational environments. In this discussion, the article details the advantages and limitations of each technology, including the voice realism of ElevenLabs and the natural language processing capabilities of OpenAI. The integration of OpenAI and ElevenLabs is expected to enhance the learning experience, while considering the financial and technical challenges that may arise.